2018
DOI: 10.1186/s12967-018-1708-z
|View full text |Cite
|
Sign up to set email alerts
|

Mutational and phenotypic spectrum of OTOF-related auditory neuropathy in Koreans: eliciting reciprocal interaction between bench and clinics

Abstract: BackgroundWhile auditory neuropathy spectrum disorder (ANSD) is a heterogeneous disorder and its management quite varies depending upon the etiology, even including self-resolution, OTOF is an important molecular etiology of prelingual ANSD and has emerged as an attractive target for implementation of precision medicine in terms of timing and prognosis prediction of auditory rehabilitation. However, to date, the literature is lacking in the genotype–phenotype relationship of this gene as well as efficient mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…In detail, OTOF variants (p.Glu841Lys, p.Arg1856Trp, p.Leu1011Pro, p.Tyr1064Ter, and p.Arg1939Gln) were highly prevalent among Korean and East Asian prelingual ANSD ( Supplementary Table S1). OTOF variants, including a founder variant (p.Arg1939Gln) among Koreans, account for approximately 90% of Korean prelingual ANSD cases with anatomically intact cochlear nerves [14]. Consistent with this, OTOF p.Arg1939Gln was found in 20 of the 26 alleles (76.9%) among Japanese congenital or early-onset ANSD cases and the founder effect was determined for this variant [21].…”
Section: Design and Establishment Of The U-top™ Hl Genotyping Kit Ver2mentioning
confidence: 56%
See 3 more Smart Citations
“…In detail, OTOF variants (p.Glu841Lys, p.Arg1856Trp, p.Leu1011Pro, p.Tyr1064Ter, and p.Arg1939Gln) were highly prevalent among Korean and East Asian prelingual ANSD ( Supplementary Table S1). OTOF variants, including a founder variant (p.Arg1939Gln) among Koreans, account for approximately 90% of Korean prelingual ANSD cases with anatomically intact cochlear nerves [14]. Consistent with this, OTOF p.Arg1939Gln was found in 20 of the 26 alleles (76.9%) among Japanese congenital or early-onset ANSD cases and the founder effect was determined for this variant [21].…”
Section: Design and Establishment Of The U-top™ Hl Genotyping Kit Ver2mentioning
confidence: 56%
“…Recent studies have shown a higher genetic load of OTOF variants explaining 91% of prelingual ANSD in Koreans with an anatomically intact cochlear nerve [14]. Furthermore, understanding the distribution pattern of the Korean OTOF alleles, which are predominantly concentrated on certain exons among Korean prelingual ANSD, could provide a justification for proposing a set of the most frequent OTOF variants to be included in the first-line screening [14,15]. As a result, the new genotyping kit developed in this study exclusively comprises the five most prevalent missense variants of OTOF causing prelingual ANSD in the Korean population, showing perfect agreement with Sanger sequencing analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Without this genetic information, HL in patients with CAPOS syndrome would be considered "central" due to the accompanying deficits of the central nervous system, precluding the implementation of CI in these subjects. OTOF-related prelingual ANSD patients are also considered to have good prognosis for CI, if CI can be performed in a very timely fashion [15]. Considering the amount of residual hearing, it would be highly unlikely to perform early CI in those patients without the genetic information.…”
mentioning
confidence: 99%